Microbial isolation from gastrointestinal tract of catfish (Clarias gariepinus) - Nurul Aini; Muhammad Bachruddin; Izdihar Tsana (Journal of Microbial Systematics and Biotechnology, 2020)
The purpose of this research was to describe the characteristics and number of microbes that grow in the gastrointestinal tract of catfish and to determine the potential of microbes as probiotics. The type of this research was observational conducted on 30 September-15October 2018 at the Microbiology Laboratory, Faculty of Science and Technology, Universitas Airlangga, Surabaya. Microbial isolation using Nutrient Agar (NA), Mann de Roosa Shrape agar (MRSA) and potato dextrose agar (PDA) media. The fish that used is catfish that are bred in ponds at Desa Tlasih, Kecamatan Tulangan, Kabupaten Sidoarjo, East Java. The identification includes microscopic and macroscopic characteristics. Based on the research that has been done, it can be concluded that there are 8 kinds of bacterial colonies in NA media, on PDA media there are 8 kinds of fungi, and on MRSA media there are 2 bacterial colonies and each has different macroscopic and microscopic characteristics. The total number of bacteria growing in NA and MRSA media respectively were 8.7 x 104 CFU/g and 1.2 x 105 CFU/g. It is suspected that there are potential bacteria as beneficial probiotics for catfish which still need further research.